The opiate dosage adequacy scale for identification of the right methadone dose—a prospective cohort study. Issue 1 (December 2016) - Walcher, Stephan; Koc, John; Reichel, Volker; Schlote, Frank; Verthein, Uwe; Reimer, Jens
Abstract Background Opioid maintenance treatment with methadone is regarded as gold standard in the therapy of opioid dependence. Identification of the 'right' methadone dose, however, remains challenging. We wanted to explore if the Opiate Dosage Adequacy Scale (ODAS) is a helpful instrument in methadone titration. Methods Within this 12-months prospective naturalistic cohort study patients in stable maintenance treatment with methadone (Eptadone®) were included. Sociodemographic and clinical data were gathered at baseline, and months 3, 6, and 12. At the same points in time, the instruments ODAS, European Addiction Severity Index (EuropASI), and Derogatis Interview for Sexual Functioning-Self Report (DISF-SR) were applied. Results Five hundred fifteen patients were enrolled, 129 patients prematurely terminated substitution treatment (treatment failure), in 108 patients substitution medication was changed, likely due to bitter taste of Eptadone®. Complete longitudinal ODAS and EuropASI data sets were available for 229 patients. The frequency of adequate methadone doses (ODAS) increased (60.9 % at baseline, 85.3 % at month 12) as well as the average daily methadone dose (63.8 (±30.8) mg/day at baseline to 69.6 (±36.0) mg/day at month 12). Inadequacy of methadone dose was not associated with treatment failure (RR 1.019; CI 95 % 0.756–1.374). Addiction severity decreased statistically significantly. Compared to adequately dosed patients, inadequately dosed patients benefited more, in that they showed greater improvements in ODAS scores, had higher increases in methadone dose, and partially experienced more advanced sexual functioning. Conclusion Application of ODAS was associated with improved methadone dose adequacy and addiction severity parameters as well as increased methadone doses. Its usefulness should be corroborated in a controlled trial.